Activity Daily Living (ADL) dan Riwayat Penyakit Kronis Terhadap Depresi Lansia di Aceh Barat Daya - Ria, Ria Komala Sari; Heri Mis Cicih, Lilis; Indriyati, Titi (Jurnal Ilmiah Kesehatan, 2025)
Depression in the elderly is a significant and common mental health concern, especially among those with limited daily activities and chronic disease histories. This study analyzed the relationship between activities of daily living (ADL) and chronic disease history with depression among the elderly in the working area of Lembah Sabil Health Center, Southwest Aceh District. A quantitative cross-sectional design was used, conducted in June–July 2025 with 101 participants. Data were collected via questionnaires and medical records, and analyzed using univariate, bivariate (chi-square), and multivariate (logistic regression) methods. Significant associations were found between ADL and depression (p = 0.000), and between chronic disease history and depression (p = 0.001). Multivariate analysis showed chronic disease history as the dominant factor (OR = 6.640). Keywords: Elderly, Depression, Activities of Daily Living, Chronic Disease